Regulatory Mechanism of C1q-Like Protein 4 in Characteristics of Breast Cancer Stem Cells - Xiao LI; Shenglin ZHANG; Chanchan HU; Lu BAI; Fan XU (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the role and underlying mechanism of C1q-like protein 4 (C1ql4) in regulating the characteristics of breast cancer stem cells. MethodsqRT-PCR was used to detect the expression of C1ql4 in breast cancer and normal breast epithelial cell lines, as well as to verify the transfection efficiency of C1ql4. Western blot analysis was employed to examine the phosphorylation levels of AKT, IKK, and IκB in different groups. An AKT activator was added to MDA-MB-231 cells with C1ql4 knockdown, whereas inhibitors targeting AKT, IKK, IκB, and NF-κB nuclear translocation were separately introduced to C1ql4-overexpressing MCF-7 cells. The nuclear translocation of NF-κB, expression levels of the target genes TNF-α and IL-1β, formation ability of tumorspheres, and proportion of CD44+/CD24−/low stem-like subgroups were analyzed. ResultsC1ql4 expression in breast cancer cell lines was significantly upregulated compared with that in normal breast epithelial cells. Western blot analysis showed that p-AKT/AKT, p-IKK/IKK, and p-IκB/IκB ratios markedly reduced in C1ql4-knockdown MDA-MB-231 cells (all P<0.05) but significantly increased in C1ql4-overexpressing MCF-7 cells (all P<0.05). Rescue experiments demonstrated that the addition of an AKT activator to C1ql4-knockdown MDA-MB-231 cells resulted in the enhanced nuclear translocation of NF-κB, the increased nuclear/cytoplasmic NF-κB ratios, the elevated TNF-α and IL-1β expression levels, and significant recovery of tumorsphere formation ability and the proportion of CD44+/CD24−/low stem-like subpopulations (all P<0.05). Conversely, in C1ql4-overexpressing MCF-7 cells, treatment with AKT, IKK, IκB, or NF-κB nuclear translocation inhibitors led to a reduction in NF-κB nuclear translocation, decreased nuclear/cytoplasmic NF-κB ratios, and declines in TNF-α and IL-1β expression levels, tumorsphere formation ability, and the CD44+/CD24−/low subpopulation (all P<0.05). ConclusionC1ql4 promotes the translocation of NF-κB from the cytoplasm to the nucleus through the PI3K/AKT/NF-κB signaling pathway and enhances the expression of stemness in breast cancer cells.